Aphantasia and psychological disorder: Current connections, defining the imagery deficit and future directions - Cavedon-Taylor, Dan (Frontiers in Psychology, 2022)
Aphantasia is a condition characterised by a deficit of mental imagery. Since several psychopathologies are partially maintained by mental imagery, it may be illuminating to consider the condition against the background of psychological disorder. After outlining current findings and hypotheses regarding aphantasia and psychopathology, this paper suggests that some support for defining aphantasia as a lack of voluntary imagery may be found here. The paper then outlines potentially fruitful directions for future research into aphantasia in general and its relation to psychopathology in particular, including rethinking use of the SUIS to measure involuntary imagery, whether aphantasia offers protection against addiction, and whether hyperphantasia is a potential risk factor for maladaptive daydreaming, among others.